Hubungan Antara Peran Ayah Pada Perkembangan Moral Remaja Di RT 29 Dan RT 40 Kecamatan Jakabaring Palembang - Andriani, Siska; Suryati, Suryati; Fitri, Hartika Utami (Journal of Innovative and Creativity, 2026)
This study, entitled "The Relationship Between Fathers' Roles and the Moral Development of Adolescents in Neighborhood Associations (RT) 29 and 40, Jakabaring District, Palembang," aims to determine the role of fathers in raising adolescents and the relationship between fathers' roles and the moral development of adolescents in RT 29 and RT 40, Jakabaring District. This study used a quantitative approach with a correlational approach. The sample size for this study was 30 respondents. Simple random sampling was used for the study, and a questionnaire was used for data analysis. SPSS version 20 was used for data processing with a product-moment correlation. The validity test level was 0.361 and the reliability test level was 0.7. The results of this study indicate that the level of fathers' role in raising adolescents is classified as moderate. 77% of adolescents received moderate scores for moral development. Meanwhile, 66% of adolescents received moderate scores for moral development. There was a significant relationship between the father's role and adolescent moral development, with a product-moment correlation of 0.771 and a significance level of 5%. The results of this study indicate a relationship between the father's role and adolescent moral development.